THE USE OF (Mg0.9Zn0.1)TiO3+2wt.% Bi2O3 CERAMICS AS A DIELECTRIC RESONATOR OSCILLATOR MATERIAL AND CHARACTERISATION OF STRUCTURE, MICROSTRUCTURE, AND DENSITY - Kadarosman, Afandy; Ermawati, Frida Ulfah (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
Magnesium titanate (MgTiO3)-based ceramics have the potential for use in the telecommunications industry at microwave frequencies, including as a resonator in dielectric resonator oscillator (DRO) circuit. This research is intended to study the application of (Mg0.9Z0.1)TiO3+2wt.% Bi2O3 (abbreviated MZT01-2) ceramics as DRO material and characterize the structure, microstructure, and bulk density. Fabrication was carried out by ball milling between (Mg0.9Z0.1)TiO3 crystalline powder and 2wt.% Bi2O3 powder. The milled powder was compacted at certain pressure using a die press to become pellets. All pellets were sintered at 1000, 1100, 1200Â°C for 4 h to obtain ceramics. The structural characterization using XRD showed that the three ceramics contained the main MgTiO3 phase, each 93.63, 93.83, and 90.78% molar, the rest was the MgTi2O5 phase. The increase in sinter temperature causes the lattice parameter and the unit cell volume to decrease. The Archimedes bulk density was 2.928; 2.832 and 2.736 g/cm3. The microstructure is solid surfaces with a grain diameter of 1.9-2.3 Î¼m accompanied by pores. As DRO materials, the three ceramics exhibited a resonant frequency at 5.11, 5.08, and 5.12 GHz which shows that the ceramics can be applied as DRO materials at microwave frequencies. The sinter temperature variation tends not to affect the resonant frequency position.